The strength-ductility synergy relating to dislocation behavior in the Ti70-VNbMoCr solid-solution alloys with VEC increasing orderly - Zaidong Xu; Baolin Wu; Jiale Man; Naifu Zou; Guosheng Duan; Yandong Liu; Yicheng Feng (Journal of Materials Research and Technology)
In the present study, a series of multi-element Ti70-VNbMoCr alloys were designed based on the maximum entropy principle with orderly increasing valence electron concentration (VEC), and the evolution of tensile properties in the alloys was experimentally investigated combing molecular dynamic (MD) modelling. The results showed that the yield strength increased in the VEC order from low to high, and the tensile plasticity decreased and then increased. Dislocation kinks were clearly observed in the deformed microstructures. In terms of the kink-strengthening mechanism and dislocation-based slip rule, the role of Burgers vector magnitude in strength-ductility synergy was discussed. It was believed that reducing Burgers vector magnitude is favorable for simultaneously enhancing both yield strength and ductility. In addition to Burgers vector magnitude, VEC played a key role in ductility. The non-monotonic variation of the tensile plasticity was attributed to the increase of VEC and reduction of Burgers vector magnitude. It was predicted that designed based on the maximum entropy principle, both tensile yield strength and plasticity would further increase in this alloy system with VEC increasing from 4.45 to 4.59 and Burgers vector magnitude reducing from 2.804 Å to 2.788 Å.